Practice and Reflection on the Interdisciplinary Teaching in Primary and Secondary Physical Education Programs - Wu, Peng (International Journal of Social Sciences and Public Administration, 2024)
This paper discusses the importance, practical strategies, advantages and challenges of implementing interdisciplinary teaching in primary and secondary physical education programmes and makes recommendations. Interdisciplinary teaching promotes students' all-round development by integrating knowledge from different disciplines. The article introduces practical cases of combining physical education with science, art, social humanities and other disciplines, and suggests that the advantages of interdisciplinary teaching include broadening horizons and enhancing fun and motivation, but it also faces the challenges of insufficient teachers' knowledge reserves and difficulties in integrating resources. To cope with these problems, this paper puts forward the following suggestions: strengthening interdisciplinary training for teachers, building teaching platforms, innovating teaching modes, and paying attention to individual student differences. Continuously promote the practice of interdisciplinary teaching, improve the quality of education, and cultivate future members of society with comprehensive qualities.